PEMBERDAYAAN MASYARAKAT DALAM MEMANFAATKAN SELF TURNING COMPOSTER SEBAGAI UPAYA MINIMASI SAMPAH DOMESTIK - Sri Slamet Mulyati -; Nurul Hidayah (Poltekkes Kemenkes Bandung, 2022)
Garbage has become a national problem so that its management needs to be carried out comprehensively. Waste that must be managed includes organic waste. Included in the efforts to improve the aeration process are turning or reversing waste and improved aeration or increasing aeration. Reversal of waste will affect the speed of composting. This Self Turning Composter is a trash chopper container as well as a garbage flipper. Inside it is installed a garbage cutting knife like the appearance of a blender equipped with a dynamo so that it can move and rotate on the outside. The use of this tool is socialized to the community so that they are motivated to carry out waste processing independently later. The results of community service showed that there was an increase in understanding of compost processing in the group of arisan women by 6.85%, and by group of recitation fathers by 5.5%. There is a positive response to the use of simple science and technology waste counting Self Turning Composter. The composting simulation process in one of the residents produces quality compost based on a direct bioassay test, which is safe when applied to plants in the residents' homes as a pilot